Such a quiet place ebook A novel. - Miranda, Megan (2021)
"An Agatha Christie vibe make[s] this whodunit an excellent beach read" ( Library Journal ). Discover secrets, scandal, and a suspected killer—all on one street in this gripping suspense from New York Times bestselling author and "master of misdirection and sudden plot twists" ( Booklist ), Megan Miranda. Welcome to Hollow's Edge, where you can find secrets, scandal, and a suspected killer—all on one street. Hollow's Edge used to be a quiet place. A private and idyllic neighborhood where neighbors dropped in on neighbors, celebrated graduation and holiday parties together, and looked out for one another. But then came the murder of Brandon and Fiona Truett. A year and a half later, Hollow's Edge is simmering. The residents are trapped, unable to sell their homes, confronted daily by the empty Truett house, and suffocated by their trial testimonies that implicated one of their own. Ruby Fletcher. And now, Ruby's back. With her conviction overturned, Ruby waltzes right back to Hollow's Edge, and into the home she shared with Harper Nash. Harper, five years older, has always treated Ruby like a wayward younger sister. But now she's terrified. What possible good could come of Ruby returning to the scene of the crime? And how can she possibly turn her away, when she knows Ruby has nowhere to go? Within days, suspicion spreads like a virus across Hollow's Edge. It's increasingly clear that not everyone told the truth about the night of the Truetts' murders. And when Harper begins receiving threatening notes, she realizes she has to uncover the truth before someone else becomes the killer's next victim. Pulsating with suspense and with Megan Miranda's trademark shocking twists, Such a Quiet Place is Megan Miranda's best novel yet—"A claustrophobic and suspenseful whodunit...that ponders the eternal question of how well we really know those closest to us" ( BookPage , starred review).